Constantine unconquered emperor, Christian victor - Stephenson, Paul ca. 20./21. Jh (Quercus, 2009)
"Constantine: Unconquered Emperor, Christian Victor is a survey of the life and legacy of the greatest of the later Roman emperors. In 312, Constantine - one of four Roman emperors ruling a divided empire - marched on Rome to establish his sole control of its western half. According to Constantine's first biographer, the bishop Eusebius, on the eve of the decisive battle, at Rome's Milvian Bridge, he had a vision. 'A cross-shaped trophy of light' appeared to him in the sky with an exhortation, generally translated as 'By this sign conquer'. Inscribing the sign on the shields of his soldiers, Constantine drove the followers of his rival Maxentius into the Tiber and claimed the imperial capital for himself. He converted to Christianity and ended persecution of his co-religionists with the defeat in 324 of his last rival, Licinius." "Under Constantine, Christianity emerged from the shadows, its adherents no longer persecuted. Constantine united the western and eastern halves of the Roman Empire, and presided over the first ecumenical council of the Christian Church, at Nicaea in 325. He founded a new capital city nearby on the Bosphorus, where Europe meets Asia. This site, the ancient trading colony of Byzantium, became the city of Constantine, Constantinople, a new Christian capital set apart from Rome's pagan past." "Paul Stephenson offers an account of a man whose cultural and spiritual renewal of the Roman Empire gave birth to the historically crucial idea of a unified Christian Europe underpinned by a commitment to religious tolerance."--BOOK JACKET.